2011
DOI: 10.1007/s10905-011-9299-z
|View full text |Cite
|
Sign up to set email alerts
|

Response of Female Frankliniella occidentalis (Pergande) to Visual Cues and Para-anisaldehyde in a Flight Chamber

Abstract: The effect of visual cue color and size, volume of para-anisaldehyde (plant-derived semiochemical), and airflow on thrips behavior were examined in a flight chamber. After 5 min more female Frankliniella occidentalis (western flower thrips) landed on sticky traps containing yellow plastic squares (100 cm 2 ) (55.2% of those that flew landed on the trap) than blue (21%), white (4.7%), or transparent traps (2%). The percentage of thrips caught on traps increased with increasing size of the visual cues (0 and 1 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
1
14
3
Order By: Relevance
“…In the present study, the largest of the green traps (40 × 25 cm) caught the highest TPP density of the four sizes used, in contrast to a previous study that reported a higher density of TPP on smaller than on larger yellow traps (Cameron et al., ). Also, trap size and trap capture of TPP in the current study did not result in a linear relationship, contrary to previous studies on Western flower thrips (Kirk, ; Vernon & Gillespie, ; Davidson et al., ). Further research comparing trap catches on several sizes of blue and yellow traps of the same shape may further elucidate the effect of trap size on TPP catches, and ultimately help identify the optimal trap size.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the present study, the largest of the green traps (40 × 25 cm) caught the highest TPP density of the four sizes used, in contrast to a previous study that reported a higher density of TPP on smaller than on larger yellow traps (Cameron et al., ). Also, trap size and trap capture of TPP in the current study did not result in a linear relationship, contrary to previous studies on Western flower thrips (Kirk, ; Vernon & Gillespie, ; Davidson et al., ). Further research comparing trap catches on several sizes of blue and yellow traps of the same shape may further elucidate the effect of trap size on TPP catches, and ultimately help identify the optimal trap size.…”
Section: Discussioncontrasting
confidence: 99%
“…() found that smaller yellow sticky traps (20 × 10 cm) caught 1.6 times more TPP per unit area than larger traps (25 × 20 cm). In contrast, studies on fruit flies (Robacker, ; Brevault & Quilici, ; Idris et al., ) and thrips (Kirk, ; Vernon & Gillespie, ; Davidson et al., ) have demonstrated increased catches per unit area with increasing trap size.…”
Section: Introductionmentioning
confidence: 93%
“…Blackmer et al (2008) found that white and blue were more attractive than yellow, whereas Yudin et al (1987) found white to be more attractive than blue or yellow. Few publications report a strong attraction to white in western flower thrips (equal as or stronger than blue) (Yudin et al, 1987; Gillespie & Vernon, 1990; Hoddle et al, 2002; Blackmer et al, 2008), and few report no attraction at all (Chen et al, 2004; Davidson et al, 2012). In a wind tunnel experiment that tested preference of a New Zealand strain of western flower thrips to various colours, more females were caught on a yellow sticky plate (55.2%) than on a blue (20.8%) or white (4.7%) plate (Davidson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The glass Y-tube olfactometer and set-up was the same as that used previously for thrips assays (Davidson et al 2006). The Y-tube has two branching arms at an angle of approximately 45° leading into a single tube (stem), all 60 mm long with an internal diameter of 5 mm.…”
Section: Materials and Methods Y-tube Olfactometer Experimentsmentioning
confidence: 99%
“…The low speed laminar flow wind tunnel was the same as that used for thrips assays (Davidson et al 2006). The Perspex® observation chamber measured 0.58 m wide by 0.55 m high by 1.7 m long and was illuminated by five 36W/840 cool lights alternating with five 36W/965 true light fluorescent tubes, producing an average of 10,000 lux (Beha, Digital Lux Hi Tester 93-1065L, Germany).…”
Section: Wind Tunnel Experimentsmentioning
confidence: 99%